Cocaine and HIV are independently associated with neural activation in response to gain and loss valuation during economic risky choice. (6th July 2017) - Meade, Christina S.; Addicott, Merideth; Hobkirk, Andrea L.; Towe, Sheri L.; Chen, Nan‐Kuei; Sridharan, Sriramkumar; Huettel, Scott A.
Abstract: Stimulant abuse is disproportionately common in HIV‐positive persons. Both HIV and stimulants are independently associated with deficits in reward‐based decision making, but their interactive and/or additive effects are poorly understood despite their prevalent co‐morbidity. Here, we examined the effects of cocaine dependence and HIV infection in 69 adults who underwent functional magnetic resonance imaging while completing an economic loss aversion task. We identified two neural networks that correlated with the evaluation of the favorable characteristics of the gamble (i.e. higher gains/lower losses: ventromedial prefrontal cortex, anterior cingulate, anterior and posterior precuneus and visual cortex) versus unfavorable characteristics of the gamble (i.e. lower gains/higher losses: dorsal prefrontal, lateral orbitofrontal, posterior parietal cortex, anterior insula and dorsal caudate). Behaviorally, cocaine and HIV had additive effects on loss aversion scores, with HIV‐positive cocaine users being the least loss averse. Cocaine users had greater activation in brain regions that tracked the favorability of gamble characteristics (i.e. increased activation to gains, but decreased activation to losses). In contrast, HIV infection was independently associated with lesser activation in regions that tracked the unfavorability of gamble characteristics. These results suggest that cocaine is associated with an overactive reward‐seeking system, while HIV is associated with an underactive cognitive control system. Together, these alterations may leave HIV‐positive cocaine users particularly vulnerable to making unfavorable decisions when outcomes are uncertain. Abstract : We examined the effects of cocaine dependence and HIV infection in 69 adults who underwent functional magnetic resonance imaging while completing an economic risk task. Cocaine was associated with greater activation in response to increasing favorability of gambles (i.e., higher gains/lower losses) in reward‐related regions (e.g., ACC and VMPFC), while HIV was associated with less activation in response to increasing unfavorability of gambles (i.e., lower gains/higher losses) in cognitive control regions (e.g., DLPFC and PPC).